1997
DOI: 10.1093/ndt/12.7.1369
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive analysis of the intestinal absorption and compartmentalization of aluminium in uraemic rats: a 26Al tracer study employing accelerator mass spectrometry

Abstract: Our data suggest that fractional absorption from a dietary level dose of 26Al is about 0.13%. Compartmentalization occurs in transferrin-dependent target tissues such as liver and spleen; however, in quantitative terms extracellular deposition in bone is more important. Uraemia has a significant effect on the intestinal absorption and compartmentalization of aluminium. It enhances fractional absorption and increases subsequent extracellular deposition of aluminium in bone. However, at the same time uraemia doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…The reason for our focus on the liver was that after the initial barrier of the intestinal wall this organ represents the second most important filter for ingested compounds. Since the uremic state is probably associated with enhanced absorption of La from the gut lumen and deposition in the liver [13,22], similarly to that reported for Al [26,27], it is not surprising that La deposition is 3- to 30-fold higher in the liver than in bone or brain [13]. …”
Section: Discussionmentioning
confidence: 90%
“…The reason for our focus on the liver was that after the initial barrier of the intestinal wall this organ represents the second most important filter for ingested compounds. Since the uremic state is probably associated with enhanced absorption of La from the gut lumen and deposition in the liver [13,22], similarly to that reported for Al [26,27], it is not surprising that La deposition is 3- to 30-fold higher in the liver than in bone or brain [13]. …”
Section: Discussionmentioning
confidence: 90%
“…Samples from muscle tissue originate from a specific part, namely the thigh, consistently over all studies. For bone, measurements generally result from femur samples (Beck 1997;Drueeke et al 1997;Jouhanneau et al 1993Jouhanneau et al , 1997Walker and Sutton 1994;Winklhofer et al 2000;Zafar et al 1997), except for Ittel et al (1997), where samples from tibia bone are analysed. Beyond the origin of the bone sample, also sample preparation varied between studies: in two studies, the bone marrow was removed (Beck 1997;Winklhofer et al 2000), while all other studies did not mention such procedure.…”
Section: Curation Of the Comprehensive Datasetmentioning
confidence: 99%
“…It was thus excluded. A total of seven studies reported summary data instead of individual observations (Drueeke et al 1997;Ittel et al 1997;Schoenholzer et al 1997;Winklhofer et al 2000;Yokel et al 2001a, b;Zafar et al 1997). Since Schoenholzer et al (1997) reported no information on the variance of the aggregated data (mean of 9 rats), we excluded this study, since the variance information is crucial for data de-aggregation.…”
Section: Curation Of the Comprehensive Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral ingestion is followed by appreciable absorption from the intestine [9,23,24] : from 0.06 to 0.1% of the amount ingested by healthy human subjects [25] . In the uremic state, intestinal uptake of aluminum and other trace elements and their deposition in bone are increased [18,[25][26][27] . Intestinal absorption also can be enhanced by zinc defi ciency [28] , a hyperparathyroid state [29][30][31] , and administration of citrate [18,24,32,33] or vitamin D [26,34] .…”
Section: Physiologic Aspects Of Exposure To Aluminummentioning
confidence: 99%